Samarbete i förskolan - Wälimaa, Ida; Vikajärvi, Annie (2011)
The present work is a thesis carried out at Luleå University, Sweden. The purpose of this study was to examine preschool teacher's approach to collaboration between the children. In order to do research on this, we used a qualitative interview with four teachers and observations of early childhood education. In our study, we have assumed the curriculum and literature studies. The result shows that preschool teachers want the cooperation will permeate their operations and that cooperation between the child's development in many different ways. The results also show that preschool teachers have been difficult to provide space for children in stressful situations and they think they should have more trust in the children in such situations. Pre-school teachers in the study believe that teachers' role is important in terms of cooperation between the children but also that teachers sometimes need to give children more space to interact on their own. Validerat; 20110817 (anonymous)